2016
DOI: 10.1007/s00192-016-3140-3
|View full text |Cite
|
Sign up to set email alerts
|

An International Urogynecological Association (IUGA)/International Continence Society (ICS) joint report on the terminology for female anorectal dysfunction

Abstract: Introduction:The terminology for anorectal dysfunction in women has long been in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
162
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(182 citation statements)
references
References 121 publications
(41 reference statements)
0
162
0
6
Order By: Relevance
“…4. Anal signs Abdominal signs Bladder fullness/retention: abdominal palpation or suprapubic percussion may indicate a full bladder; however, in overweight patients this may not be easily detected. Pelvic bone irregularities: indication of a previous fracture or sacral agenesis. 6.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4. Anal signs Abdominal signs Bladder fullness/retention: abdominal palpation or suprapubic percussion may indicate a full bladder; however, in overweight patients this may not be easily detected. Pelvic bone irregularities: indication of a previous fracture or sacral agenesis. 6.…”
Section: Assessmentmentioning
confidence: 99%
“… Local (fissures, hemorrhoids) Fecal incontinence Obstructed defecation syndrome Rectocele Enterocele/sigmoidocele Intussusception Internal mucosal prolapse Abscess/fistula …”
Section: Diagnosesmentioning
confidence: 99%
“…11 The women were categorized into four groups according to parity, mode of delivery, and OASIS; nulliparous women, women who had delivered by CS only, women with one or more VD with no OASIS, and women with one or more VD with OASIS. Flatus incontinence was defined as any involuntarily loss of flatus (gas) weekly or more frequently during the previous month.…”
Section: Materials and Me Thodsmentioning
confidence: 99%
“…8 Anal continence is a complex physiological mechanism dependent on factors such as bowel disease, bowel habits, cortical awareness, integrity of the pelvic floor muscles, and the anal sphincter muscles in particular, as well as a number of psychological factors. 11 Previous studies have reported that a disturbance in bowel habits and pelvic floor disorders such as AI, fecal urgency, constipation, and pelvic organ prolapse often co-occur, and the quality of life of women experiencing more than one pelvic floor disorder is affected. Fecal urgency is defined as having difficulty deferring a sudden or compelling desire to defecate.…”
Section: Introductionmentioning
confidence: 99%
“…Obstetric anal sphincter injuries (OASIS) are serious complications to vaginal deliveries, with a 50% long‐term risk of anal incontinence, that is, involuntary loss of feces or flatus . In Norway, a National prevention program aiming at reducing the incidence of OASIS was initiated in 2004.…”
Section: Introductionmentioning
confidence: 99%